Level of Insight in Patients With Obsessive–Compulsive Disorder: An Exploratory Comparative Study Between Patients With “Good Insight” and “Poor Insight” - de Avila, Richard Chuquel Silveira; do Nascimento, Laura Gratsch; Porto, Rafaella Landell de Moura; Fontenelle, Leonardo; Filho, Eurípedes Constantino Miguel; Brakoulias, Vlasios; Ferrão, Ygor Arzeno (Frontiers in Psychiatry, 2019)
Introduction: Insight may be defined as the ability to perceive and evaluate external reality and to separate it from its subjective aspects. It also refers to the ability to self-assess difficulties and personal qualities. Insight may be a predictor of success in the treatment of obsessive–compulsive disorder (OCD), so that individuals with poor insight tend to become refractory to treatment. The objective of this study is to investigate factors associated with poor insight in individuals with OCD. Methods: This cross-sectional exploratory study used the Brown Belief Assessment Scale as a parameter for the creation of the comparison groups: individuals who obtained null scores (zero) composed the group with preserved or good insight (n = 148), and those with scores above the 75% percentile composed the group with poor insight (n = 124); those with intermediate scores were excluded. Sociodemographic characteristics and clinical and psychopathological aspects, intrinsic and extrinsic to the typical symptoms of OCD, were compared in a univariate analysis. A logistic regression was used to determine which factors associated with critical judgment remained significant. Results: Individuals in the poor insight group differed from those with good insight in regard to: more prevalent use of neuroleptics (p = 0.05); higher untreated time interval (p < 0.001); higher total Yale–Brown obsessive–compulsive scale score and the obsessions and compulsions factors (all factors with p < 0.001); higher dimensional Yale–Brown obsessive–compulsive scale total and dimensional scores (p from 0.04 to 0.001); higher prevalence of contamination/cleaning (p = 0.006) and hoarding (p < 0.001) symptoms dimensions; more prevalent sensory phenomena (p = 0.023); higher levels of depression (p = 0.007); and more prevalent comorbidity with bipolar affective disorder (p = 0.05) and post-traumatic stress disorder (PTSD) (p = 0.04). After analyzing the logistic regression, we conclude that the most important factors associated with poor insight are: the presence of any sensory phenomena (OR: 2.24), use of neuroleptics (OR: 1.66), and hoarding symptoms (OR: 1.15). Conclusion: The variability of insight in patients with OCD seems to be an important psychopathological characteristic in the differentiation of possible subtypes of OCD, since the poor insight is associated with sensory phenomena and greater use of neuroleptics, which makes it possible to conjecture the role of dopaminergic neurocircuits in the neurobiology of this disorder. In addition, there is also an association with the symptoms of hoarding content, admittedly one of the symptomatic contents with less response to conventional OCD treatments. Studies based on neurobiological aspects such as neuroimaging and neuropsychology may help to elucidate more consistently the role of insight in patients with OCD and the repercussions concerning available treatments.